1999
DOI: 10.1111/j.1151-2916.1999.tb02003.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Surface Residual Stresses in Brittle Materials by Hertzian Indentation: Theory and Experiment

Abstract: Hertzian indentation has been used to determine the surface residual stress levels in brittle materials. In this method, a hard sphere is pressed into the surface of the material: at a critical load a preexisting surface-breaking crack in the neighborhood of the contact will propagate. There is a threshold load below which no such crack, of whatever size, can be propagated. The presence of a residual stress in the surface will lead to a shift in this threshold load. The effects of residual stresses on the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…These data can be used to estimate the surface residual stresses [24]. Data were analysed by calculating the effects of biaxially compressed surface layers of varying stress level and depth on the results of the Hertzian tests.…”
Section: Resultsmentioning
confidence: 99%
“…These data can be used to estimate the surface residual stresses [24]. Data were analysed by calculating the effects of biaxially compressed surface layers of varying stress level and depth on the results of the Hertzian tests.…”
Section: Resultsmentioning
confidence: 99%
“…Before this higher load is reached the fracture of the sand particles may occur, thereby preventing that load from being attained. Roberts et al [28,29] have investigated the effect of compressive residual stress on the fracture load in a Hertz indentation test indenting glass with a 10 mm diameter glass ball. They found that as the surface compressive stress increased from 0 (nominally "stress free") to 500 MPa the minimum fracture load increased by more than an order of magnitude.…”
Section: Comparison Of Crack Diameters With Hertz Impact Theorymentioning
confidence: 99%
“…For the case of a material with residual stress, the value of µ is affected by the relative value of these residual stresses with respect to peak indentation pressure. 38 If this relative value is lower than 20%, the modified value of µ by the residual stresses, labelled as µ , can be related through the value of µ without residual stresses by the approximation: µ = µb −σ r /P 1/3 (14) where b is a constant, which depends on the elastic properties of the material and the indenter. Using this relationship for µ , a similar relationship as Eq.…”
Section: Discussionmentioning
confidence: 99%